The chronicles of Nazareth (the English convent), Bruges 1629 - 1793 - Bowden, Caroline (London : Catholic Record Society, 2017)
The English Augustinian Canonesses at Bruges kept records of daily life and key events in their convent from its foundation in 1629. Living in exile, members of the convent were well-aware of their importance to the survival of English Catholicism for women. Keeping full records served to maintain a reputation which would attract influential and wealthy benefactors and well-qualified members; but they are far more than window-dressing. They introduce the reader to members at every level, from impressive community leaders to candidates who failed to live up to expectations and were tactfully nudged out before profession. We meet Prioresses who take on major challenges in fund-raising to pay for building projects, manage disagreements over spiritual direction and adjust to new relationships with secular authorities, the impact of the Enlightenment and finally war. There are some intense personal dramas that unfold alongside nuns who followed the monastic rule to the letter and served the community faithfully over many years. The Chronicles edited in this volume, taking the story to the eighteenth century and a decision as to whether or not to return to England, are presented with introduction and full notes.
Keywords: 27179*7 -- Reguliere kanunniken en kanunnikessen van S Augustinus Orde van het H Graf Victorinen